EFFECT OF SOME NOVEL INSECTICIDES ON LARVAL POPULATION OF GRAM POD BORER, HELICOVERPA ARMIGERA A ARMIGERA A ARMIGERA (HUB.) IN CHICKPEA - KUMAR, SUDHIR; SINGH, GAJE; KUMAR, DEEPAK (The Bioscan, 2016)
A field experiment was conducted in randomized block design with three replications of seven treatments during Rabi season 2010-11 at entomological research block of crop research centre, Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.) to evaluate the effect of some novel insecticides against the H. armigera in chickpea. Efficacy of six insecticides viz., Indoxacarb 14.5 SC @ 500 ml/ha, Cypermethrin 25 EC @1000 ml/ha, Lambda cyhalothrin 5 EC @ 500 ml/ha, Thiodicarb 75 WP @ 625 gm/ha, Spinosad 45 SC @ 200 ml/ha and Carbosulfan 25 EC @ 1000 ml/ha tested against H. armigera larvae. The treatment with Indoxacarb 14.5 SC @ 500 ml/ha was found best with minimum population of H. armigera at first spray 1.33 (3 DAS) and 2.00 larvae/five plants (9 DAS), and the minimum larval population at second spray 1.67 (3 DAS) and 3.33 larvae/ five plants (9 DAS). The Cypermethrin 25 EC @1000 ml/ha was recorded less effective among all the treatments, though it was statistically superior to the untreated control. The result revealed that Indoxacarb 14.5 SC @ 500 ml/ha was found best to minimizing the larval population after the both insecticidal spray.